Innovative engineering robots in today's paper manufacturing industry (SHOPWARE, 2000)
This video examines how robots have been used to revolutionize the paper manufacturing industry. Viewers see various robots performing a multitude of tasks with efficiency and accuracy, and gain a better understanding of how robots are changing the way we work today. Includes interviews with various robotics manufacturers in Germany, Sweden and the U.S. who produce robots for industries around the world.